Robotic thoracic surgery: lessons learned from the first 1,000 procedures - Durand, Marion; Nguyen, Lee S.; Mbadinga, Frankie; Pryshchepau, Maksim; Portefaix, Hadrien; Chaabane, Nouha; Ropert, Stanislas; Khen-Dunlop, Naziha (Frontiers in Surgery, 2024)
IntroductionThe aim of this study was to evaluate the impact of the thoracic robotic approach in a high-volume center regarding procedures and clinical outcomes after 1,000 procedures.MethodsIn a single-center subset of the Epithor® database, a prospective cohort database of French thoracic surgery, we analyzed procedural characteristics and clinical outcomes from February 2014 to April 2023. A surgical technique for lung surgery was conducted with a four-arm closed chest with the port access approach and vascular sewing and knotting were preferred over stapling. Statistical analysis was performed using the Chi-2 test for discontinuous variables and the Mann–Whitney–Wilcoxon test for continuous variables. Tests were considered significant for a p-value <0.05.ResultsRobotic thoracic surgery was used in anatomical lung resection in 85% of the cases. Over the study period, 1,067 patients underwent robotic surgery, of which 509 had lobectomies and 391 segmentectomies. In the segmentectomy group vs. lobectomy group we observed a shorter length of stay (9 ± 7 vs. 7 ± 5.6 days, p < 0.001), a shorter surgery time (99 ± 24 vs. 116 ± 38 min, p < 0.001) a lower conversion rate (n = 2 vs. n = 17, p = 0.004), and a lower complication rate (28% vs. 40%, p = 0.009, mainly Clavien–Dindo II, 18% and 28%, respectively). For cancer treatment surgery, we found more previous cancer in the segmentectomy group (48% vs. 26%, p < 0.001). We also observed a progressive change of lobectomy vs. segmentectomy from 80%/20% to 30%/70% over the 9 years.DiscussionA robotic platform is an appropriate tool to perform anatomical lung resection and especially to develop a safe and systematic approach to lung-sparing sub-lobar resection.